Diagnostic Performance of a Lower‐dose Contrast‐Enhanced 4D Dynamic MR Angiography of the Lower Extremities at 3 T Using Multisegmental Time‐Resolved Maximum Intensity Projections. Issue 3 (7th April 2021) - Raczeck, Paul; Fries, Peter; Massmann, Alexander; Minko, Peter; Frenzel, Felix; Woerner, Tobias; Buecker, Arno; Schneider, Guenther K.
Abstract : Background: For peripheral artery disease (PAD), MR angiography (MRA) is a well‐established diagnostic modality providing morphologic and dynamic information comparable to digital subtraction angiography (DSA). However, relatively large amounts of contrast agents are necessary to achieve this. Purpose: To evaluate the diagnostic accuracy of time‐resolved 4D MR‐angiography with interleaved stochastic trajectories (TWIST‐MRA) by using maximum intensity projections (MIPs) of dynamic images acquired with reduced doses of contrast agent. Study Type: Retrospective. Population: Forty adult PAD patients yielding 1088 artery segments. Field Strength/Sequence: A 3.0 T, time‐resolved 4D MR‐angiography with TWIST‐MRA and MIP of dynamic images. Assessment: DSA was available in 14 patients (256 artery segments) and used as reference standard. Three‐segmental MIP reconstructions of TWIST‐images after administration of 3 mL of gadolinium‐based contrast agent (Gadoteridol/Prohance®, 0.5 M) per anatomical level (pelvis, thighs, and lower legs) yielded 256 artery segments for correlation between MRA and DSA. Three independent observers rated image quality (scale: 1 [nondiagnostic] to 4 [excellent]) and the degree of venous overlay (scale: 0 [none] to 2 [significant]) for all segments. Diagnostic accuracy for the detection of >50% stenosis and artery occlusion was calculated for all observers. Statistical Tests: Binary classification test (sensitivity, specificity, positive/negative predictive values, diagnostic accuracy). Intraclass correlation coefficients (ICCs), logistic regression analysis with comparison of areas under the receiver‐operating‐characteristics (ROC) curves (AUCs) with the DeLong method. Bland–Altman‐comparison. Results: High diagnostic performance was achieved for the detection of >50% stenosis (sensitivity 92.9% [84.3–99.9% (95%‐CI)] and specificity 98.5% [95.7–99.8% (95%‐CI)]) and artery occlusion (sensitivity 93.1% [77.2–99.2% (95%‐CI)] and specificity 99.1% [96.9–99.9% (95%‐CI)]). Inter‐reader agreement was excellent with ICC values ranging from 0.95 to 1.0 for >50% artery stenosis and occlusion. Image quality was good to excellent for both readers (3.41 ± 0.72, 3.33 ± 0.65, and 3.38 ± 0.61 [mean ± SD]) with good correlation between observer ratings (ICC 0.71–0.81). No significant venous overlay was observed (0.06 ± 0.24, 0.23 ± 0.43 and 0.11 ± 0.45 [mean ± SD]). Data Conclusion: MIPs of dynamic TWIST‐MRA offer a promising diagnostic alternative necessitating only reduced amounts (50%) of gadolinium‐based contrast agents for the entire runoff vasculature. Evidence Level: 3 Technical Efficacy: Stage 2